Modified chemical corrosion resistant ABS material and preparation method thereof

CN120245558BActive Publication Date: 2026-10-23SUZHOU ANMEI MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510419465.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-23
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

[0005]尽管上述改性技术取得了一定成效,但仍面临一些技术挑战:纳米填料在ABS基体中的分散均匀性直接影响材料的性能稳定性,需进一步优化分散工艺;现有表面处理技术的耐久性不足,长期使用后易失效,需开发更耐久的保护层

Benefits of technology

[0023]1.本发明通过在ABS基体中引入梯度分布的纳米片状防腐材料,构建从表面到内部防腐材料浓度逐渐降低的梯度结构,表面高浓度的防腐材料可以有效阻隔腐蚀介质的渗透,而内部较低的浓度则保证了材料的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005344814270000101
    Figure BDA0005344814270000101
Patent Text Reader

Abstract

The application provides a modified chemical corrosion resistant ABS material, which comprises an ABS base material and a xanthan gum / polyethylene imine electrostatic spinning film, the xanthan gum / polyethylene imine electrostatic spinning film is blended from silica, xanthan gum and polyethylene imine, and both sides of the electrostatic spinning film are loaded with nanosheet materials with different densification. The application achieves the effect of acid and alkali corrosion resistance by designing gradient distribution of anticorrosion fillers and combining the synergistic effect of the swellable electrostatic spinning film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a modified chemical corrosion resistant ABS material and its preparation method. Background Technology

[0002] ABS (acrylonitrile-butadiene-styrene copolymer), as a thermoplastic engineering plastic with excellent comprehensive properties, is widely used in automobiles, electronics, and building materials due to its combination of the chemical resistance of acrylonitrile, the toughness of butadiene, and the processability of styrene. However, its chemical corrosion resistance has significant limitations, especially in strong acid, strong alkali, and some organic solvent environments, where it is prone to swelling, stress cracking, and even structural damage. This has become a core bottleneck restricting its expansion into high-end applications such as chemical equipment and storage of highly corrosive media.

[0003] To improve the chemical corrosion resistance of ABS materials, researchers have conducted in-depth explorations through various modification techniques, including blending modification, surface treatment, nanofiller reinforcement, and chemical grafting modification.

[0004] Blending modification is a common method to improve the chemical corrosion resistance of ABS. By blending ABS with other high-performance polymers (such as polycarbonate PC and polyamide PA) to form alloys, its chemical resistance and mechanical properties can be significantly improved. For example, PC / ABS alloys not only have excellent heat resistance and impact resistance, but also effectively resist the erosion of corrosive media such as acids and alkalis. In addition, researchers have also tried blending ABS with engineering plastics such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) to further optimize its chemical corrosion resistance. Surface treatment technology improves chemical corrosion resistance by forming a protective layer on the ABS surface to block the penetration of corrosive media. Common surface treatment methods include electroplating, coating, and chemical grafting. The introduction of nanofillers has become an important research direction for modified ABS materials in recent years. By adding nanomaterials such as nanoclay and graphene, the mechanical properties and chemical corrosion resistance of ABS can be significantly improved. For example, the uniform dispersion of nanoclay in the ABS matrix can effectively block the penetration of corrosive media while enhancing the strength and hardness of the material. Furthermore, the addition of graphene not only improves the electrical conductivity and thermal stability of ABS, but also significantly enhances its acid and alkali resistance. Chemical grafting modification improves the chemical corrosion resistance by altering the molecular structure of ABS and introducing functional groups. For example, researchers have significantly improved the acid and alkali resistance of ABS by grafting fluorine-containing groups onto the ABS molecular chain.

[0005] Despite the achievements of the above-mentioned modification technologies, some technical challenges remain: the uniformity of the dispersion of nanofillers in the ABS matrix directly affects the performance stability of the material, and the dispersion process needs to be further optimized; the durability of existing surface treatment technologies is insufficient, and they are prone to failure after long-term use, so a more durable protective layer needs to be developed. Summary of the Invention

[0006] The technical problem to be solved: The purpose of this invention is to provide a modified chemical corrosion resistant ABS material and its preparation method. By designing a gradient distribution of anti-corrosion filler and combining it with a swellable electrospun film, the effect of acid and alkali corrosion resistance is achieved.

[0007] Technical solution: A modified chemical corrosion resistant ABS material, the ABS material comprising an ABS substrate and a xanthan gum / polyethyleneimine electrospun film, the xanthan gum / polyethyleneimine electrospun film being composed of a blend of silica, xanthan gum and polyethyleneimine, and the two sides of the electrospun film being loaded with nanosheet materials of different densification.

[0008] Preferably, the nanosheet material includes any one or more of graphene, hexagonal boron nitride, molybdenum disulfide nanosheets, montmorillonite nanosheets, or layered montmorillonite.

[0009] Preferably, the method for preparing the xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0010] S11. Provides xanthan gum aqueous solution, polyethyleneimine aqueous solution and porous silica micro / nano particles;

[0011] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution one after another and mixed evenly to obtain mixed spinning solution;

[0012] S13. Electrospin the mixed spinning solution to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun film;

[0013] S14. The uncrosslinked xanthan gum / polyethyleneimine electrospun membrane is placed in a desiccator containing glutaraldehyde to undergo a crosslinking reaction, thereby obtaining the xanthan gum / polyethyleneimine electrospun membrane.

[0014] Preferably, the xanthan gum aqueous solution has a weight-average molecular weight of 20,000–30,000 and a concentration of 1–3 wt%; and / or, the polyethyleneimine aqueous solution has a weight-average molecular weight of 80,000–100,000 and a concentration of 40–60 wt%; and / or, the mass ratio of the polyethyleneimine aqueous solution, xanthan gum aqueous solution, and porous silica micro / nanoparticles is 30–50:10:3–5. Preferably, the electrospinning parameters are a spinning voltage of 15–20 kV, a flow rate of 0.2–0.3 mL / h, and a receiving distance of 15–18 cm.

[0015] The above-mentioned method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0016] S1. Styrene and acrylonitrile are mixed evenly, then nanosheet material and photoinitiator are added and dispersed evenly to obtain a high-concentration solution;

[0017] S2. After mixing styrene and acrylonitrile evenly, add nanosheet material and photoinitiator, disperse evenly, and obtain a low-concentration solution;

[0018] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun film with solutions of different high and low concentrations to obtain a composite electrospun film; S4. Composite the composite electrospun film with ABS sheet, using the side coated with the low concentration solution to composite with the ABS sheet, and then subject it to ultraviolet irradiation to obtain a modified chemical corrosion resistant ABS material.

[0019] Preferably, in step S1, the mass ratio of styrene, acrylonitrile, photoinitiator, and nanosheet material is 30-40:10-20:5-8:1-2.

[0020] Preferably, in step S2, the mass ratio of styrene, acrylonitrile, photoinitiator, and nanosheet material is 30-40:10-20:3-4:1-2.

[0021] Preferably, the ultraviolet irradiation time in step S3 is 10-15 minutes.

[0022] Beneficial effects: The modified chemical corrosion resistant ABS material of this invention has the following advantages:

[0023] 1. This invention introduces a gradient distribution of nanosheet-like anti-corrosion material into an ABS matrix to construct a gradient structure in which the concentration of anti-corrosion material gradually decreases from the surface to the interior. The high concentration of anti-corrosion material on the surface can effectively block the penetration of corrosive media, while the lower concentration in the interior ensures the mechanical properties of the material.

[0024] 2. In this invention, the swelling characteristics of materials in electrospun membranes are utilized. In an acidic environment, polyethyleneimine undergoes controllable swelling to form a dense protective layer, thereby preventing further penetration of corrosive media. At the same time, high specific surface area silica is added to the electrospun membrane. Silica reduces the penetration rate of acidic and alkaline substances through physical adsorption, thereby improving the chemical corrosion resistance of the material.

[0025] 3. In this invention, the gradient densification structure can effectively slow down the penetration rate of corrosive media and provide initial protection for the material; the swelling material swells under the action of corrosive media, filling the micropores and defects on the material surface to form a dense protective layer, further preventing the penetration of corrosive media. The synergistic effect of the two mechanisms can significantly improve the chemical corrosion resistance of the material and extend its service life. Detailed Implementation

[0026] The present invention will be further described below with reference to embodiments. These embodiments are illustrative of the present invention, but the present invention is not limited to these embodiments:

[0027] Example 1

[0028] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0029] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 30:10:5:1. Disperse evenly to obtain a high-concentration solution.

[0030] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 30:10:3:1. Disperse evenly to obtain a low-concentration solution.

[0031] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0032] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 10 minutes to obtain modified chemical corrosion resistant ABS material.

[0033] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0034] S11. Provide an aqueous solution of xanthan gum with a concentration of 1 wt%, an aqueous solution of polyethyleneimine with a concentration of 40 wt%, and a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 80,000, xanthan gum with a weight-average molecular weight of 20,000.

[0035] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 30:10:3. Mix them evenly to obtain a mixed spinning solution.

[0036] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 15kV, flow rate of 0.2mL / h, and receiving distance of 15cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0037] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0038] Example 2

[0039] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0040] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 40:20:8:2. Disperse evenly to obtain a high-concentration solution.

[0041] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 40:20:4:2. Disperse evenly to obtain a low-concentration solution.

[0042] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0043] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0044] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0045] S11. Provide a 3wt% xanthan gum aqueous solution, a 60wt% polyethyleneimine aqueous solution, and a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 100,000, xanthan gum with a weight-average molecular weight of 30,000.

[0046] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 50:10:5. Mix them evenly to obtain a mixed spinning solution.

[0047] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 20kV, flow rate of 0.3mL / h, and receiving distance of 18cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0048] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0049] Example 3

[0050] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0051] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a high-concentration solution.

[0052] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:3.5:1.2. Disperse evenly to obtain a low-concentration solution.

[0053] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0054] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0055] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0056] S11. Provide a 2wt% xanthan gum aqueous solution, a 50wt% polyethyleneimine aqueous solution, and a solution with a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 80,000, xanthan gum with a weight-average molecular weight of 25,000.

[0057] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution.

[0058] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0059] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0060] Example 4

[0061] The difference between Example 4 and Example 3 is that the specific surface area of ​​the porous silica micro / nanoparticles is 750 m². 2 / g;

[0062] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0063] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a high-concentration solution.

[0064] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:3.5:1.2. Disperse evenly to obtain a low-concentration solution.

[0065] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0066] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0067] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0068] S11. Provide a 2wt% xanthan gum aqueous solution, a 50wt% polyethyleneimine aqueous solution, and a specific surface area of ​​750 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 80,000, xanthan gum with a weight-average molecular weight of 25,000.

[0069] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution.

[0070] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0071] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0072] Example 5

[0073] The difference between Example 5 and Example 3 is that the specific surface area of ​​the porous silica micro / nanoparticles is 950 m². 2 / g;

[0074] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0075] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a high-concentration solution.

[0076] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:3.5:1.2. Disperse evenly to obtain a low-concentration solution.

[0077] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0078] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0079] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0080] S11. Provide an aqueous solution of xanthan gum with a concentration of 2 wt%, an aqueous solution of polyethyleneimine with a concentration of 50 wt%, and a specific surface area of ​​950 m². 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 80,000, xanthan gum with a weight-average molecular weight of 25,000.

[0081] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution.

[0082] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0083] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0084] Comparative Example 1

[0085] The difference between Comparative Example 1 and Example 3 is that the specific surface area of ​​the porous silica micro / nanoparticles is 200 m². 2 / g.

[0086] Comparative Example 2

[0087] The difference between Comparative Example 1 and Example 3 is that solid nano-silica particles are added instead of porous silica micro / nano particles.

[0088] Comparative Example 3

[0089] The difference between Comparative Example 3 and Example 3 is that both sides of the xanthan gum / polyethyleneimine electrospun film are coated with a mixed solution of the same concentration;

[0090] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0091] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a mixed solution.

[0092] S2. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with the mixed solution to obtain a composite electrospun membrane;

[0093] S3. Composite electrospun film and ABS sheet are combined, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0094] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0095] S11. Provide an aqueous solution of xanthan gum with a concentration of 2 wt%, an aqueous solution of polyethyleneimine with a concentration of 50 wt%, and a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight average molecular weight of 80000, xanthan gum with a weight average molecular weight of 25000; S12. The porous silica micro-nano particles and polyethyleneimine aqueous solution are added to the xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution;

[0096] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0097] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0098] Comparative Example 4

[0099] The difference between Comparative Example 4 and Example 3 is that the xanthan gum / polyethyleneimine electrospun film is coated with a mixed solution on one side.

[0100] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0101] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a mixed solution.

[0102] S2. After mixing styrene and acrylonitrile evenly, add a photoinitiator. The mass ratio of styrene, acrylonitrile and photoinitiator is 35:15:1.2. Disperse evenly to obtain a St / AN solution.

[0103] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with a mixed solution and a St / AN solution, respectively, to obtain a composite electrospun membrane;

[0104] S4. Composite electrospun film and ABS sheet are combined by coating the side coated with St / AN solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0105] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0106] S11. Provide an aqueous solution of xanthan gum with a concentration of 2 wt%, an aqueous solution of polyethyleneimine with a concentration of 50 wt%, and a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 80,000, xanthan gum with a weight-average molecular weight of 25,000.

[0107] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution.

[0108] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0109] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0110] Comparative Example 5

[0111] The difference between Comparative Example 5 and Example 3 is that the xanthan gum / polyethyleneimine electrospun film is replaced with a polyacrylonitrile electrospun film; the preparation method of the modified chemical corrosion resistant ABS material includes the following steps:

[0112] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a high-concentration solution.

[0113] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:3.5:1.2. Disperse evenly to obtain a low-concentration solution.

[0114] S3. Coat both sides of the polyacrylonitrile electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0115] S4. Composite electrospun film and ABS sheet are combined by coating the side coated with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0116] Comparative Example 6

[0117] The difference between Comparative Example 6 and Example 3 is that the weight-average molecular weight of polyethyleneimine is 20,000.

[0118] A method for preparing modified chemical corrosion resistant ABS material includes the following steps:

[0119] S1. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:6:1. Disperse evenly to obtain a high-concentration solution.

[0120] S2. After mixing styrene and acrylonitrile evenly, add hexagonal boron nitride and photoinitiator. The mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 35:15:3.5:1.2. Disperse evenly to obtain a low-concentration solution.

[0121] S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane;

[0122] S4. Composite electrospun film and ABS sheet are combined by coating the side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation for 15 minutes to obtain modified chemical corrosion resistant ABS material.

[0123] The preparation method of xanthan gum / polyethyleneimine electrospun film includes the following steps:

[0124] S11. Provide a 2wt% xanthan gum aqueous solution, a 50wt% polyethyleneimine aqueous solution, and a solution with a specific surface area of ​​550 m² / g. 2 / g porous silica micro-nano particles, polyethyleneimine with a weight-average molecular weight of 20000, xanthan gum with a weight-average molecular weight of 25000.

[0125] S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution in sequence. The mass ratio of polyethyleneimine aqueous solution, xanthan gum aqueous solution and porous silica micro-nano particles is 40:10:4. Mix them evenly to obtain a mixed spinning solution.

[0126] S13. The mixed spinning solution is electrospun. The electrospinning parameters are: spinning voltage of 18kV, flow rate of 0.3mL / h, and receiving distance of 16cm, to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun membrane.

[0127] S14. Place the uncrosslinked xanthan gum / polyethyleneimine electrospun membrane in a desiccator containing glutaraldehyde for a crosslinking reaction for 12 hours to obtain the xanthan gum / polyethyleneimine electrospun membrane.

[0128] Tensile strength was tested in accordance with GB / T1447-2005. The tensile specimen was of type I dumbbell shape, the tensile rate was 10 mm / min, and the gauge length was 50 mm.

[0129] Unnotched impact strength was tested according to GB / T1043.1-2008. The impact direction was parallel to the width of the specimen. The support lines of the long strip specimen with a length of 80 mm, a width of 10 mm, and a height of 4 mm were spaced 62 mm apart.

[0130] The tests in the examples and comparative examples were placed in hydrochloric acid at pH=2 and sodium hydroxide at pH=12. After 168 hours, the tensile strength and impact strength were tested.

[0131] Table 1 shows the mechanical properties of the samples prepared in the examples and comparative examples.

[0132] Example 1 50.7 13.2 Example 2 49.1 12.9 Example 3 51.4 13.0 Example 4 50.9 12.7 Example 5 51.1 13.3 Comparative Example 1 50.6 13.1 Comparative Example 2 48.8 12.6 Comparative Example 3 51.3 12.9 Comparative Example 4 50.9 13.3 Comparative Example 5 52.0 12.9 Comparative Example 6 51.6 12.7

[0133] Table 2 shows the mechanical properties of the samples from the examples and comparative examples after acid and alkali treatment.

[0134]

[0135] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A modified chemical corrosion resistant ABS material, characterized in that: The ABS material includes ABS sheets and xanthan gum / polyethyleneimine electrospun membranes. The xanthan gum / polyethyleneimine electrospun membrane is composed of a blend of silica, xanthan gum, and polyethyleneimine. The silica is high-specific-surface-area porous silica micro / nanoparticles. The electrospun membrane has nanosheets of different densification levels loaded on both sides. The method for preparing the electrospun membrane with nanosheets of different densification levels loaded on both sides includes the following steps: S1. Styrene and acrylonitrile are mixed evenly, then nanosheet material and photoinitiator are added and dispersed evenly to obtain a high-concentration solution; S2. After mixing styrene and acrylonitrile evenly, add nanosheet material and photoinitiator, disperse evenly, and obtain a low-concentration solution; S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane; In step S1, the mass ratio of styrene, acrylonitrile, photoinitiator and nanosheet material is 30~40:10~20:5~8:1~2. In step S2, the mass ratio of styrene, acrylonitrile, photoinitiator, and nanosheet material is 30~40:10~20:3~4:1~2.

2. The modified chemical corrosion resistant ABS material according to claim 1, characterized in that: The nanosheet material includes any one or more of graphene, hexagonal boron nitride, molybdenum disulfide nanosheets, or montmorillonite nanosheets.

3. The modified chemical corrosion resistant ABS material according to claim 1, characterized in that: The preparation method of the xanthan gum / polyethyleneimine electrospun film includes the following steps: S11. Provides xanthan gum aqueous solution, polyethyleneimine aqueous solution and porous silica micro / nanoparticles; S12. Porous silica micro-nano particles and polyethyleneimine aqueous solution are added to xanthan gum aqueous solution one after another and mixed evenly to obtain mixed spinning solution; S13. Electrospin the mixed spinning solution to obtain an uncrosslinked xanthan gum / polyethyleneimine electrospun film; S14. The uncrosslinked xanthan gum / polyethyleneimine electrospun membrane is placed in a desiccator containing glutaraldehyde to undergo a crosslinking reaction, thereby obtaining a xanthan gum / polyethyleneimine electrospun membrane.

4. The modified chemical corrosion resistant ABS material according to claim 3, characterized in that: The xanthan gum aqueous solution has a weight-average molecular weight of 20,000-30,000 and a concentration of 1-3 wt%; and / or, The polyethyleneimine aqueous solution has a weight-average molecular weight of 80,000 to 100,000 and a concentration of 40 to 60 wt%; and / or, The mass ratio of the polyethyleneimine aqueous solution, xanthan gum aqueous solution, and porous silica micro / nanoparticles is 30-50:10:3-5.

5. The modified chemical corrosion resistant ABS material according to claim 3, characterized in that: The electrospinning parameters are: spinning voltage of 15~20kV, flow rate of 0.2~0.3mL / h, and receiving distance of 15~18cm.

6. The method for preparing the modified chemically resistant ABS material according to claim 1, characterized in that, Includes the following steps: S1. Styrene and acrylonitrile are mixed evenly, then nanosheet material and photoinitiator are added and dispersed evenly to obtain a high-concentration solution; S2. After mixing styrene and acrylonitrile evenly, add nanosheet material and photoinitiator, disperse evenly, and obtain a low-concentration solution; S3. Coat both sides of the xanthan gum / polyethyleneimine electrospun membrane with solutions of different high and low concentrations to obtain a composite electrospun membrane; S4. Composite electrospun film and ABS sheet are combined by coating one side with a low concentration solution with the ABS sheet, and then subjected to ultraviolet irradiation to obtain modified chemical corrosion resistant ABS material.

7. The method for preparing the modified chemical corrosion resistant ABS material according to claim 6, characterized in that: In step S1, the mass ratio of styrene, acrylonitrile, photoinitiator, and nanosheet material is 30~40:10~20:5~8:1~2.

8. The method for preparing the modified chemical corrosion resistant ABS material according to claim 6, characterized in that: In step S2, the mass ratio of styrene, acrylonitrile, photoinitiator, and nanosheet material is 30~40:10~20:3~4:1~2.

9. The method for preparing the modified chemical corrosion resistant ABS material according to claim 6, characterized in that: The ultraviolet irradiation time in step S3 is 10-15 minutes.

Citation Information

Patent Citations

  • Preparation method of PVA (Polyvinyl Acetate) / PEI (Polyethylenimine)-T nanofiber membrane capable of specifically adsorbing mercury ions

    CN103113605A

  • Preparation method and application of micro-nano fiber membrane containing high-density amido and centrifugal spun yarns of micro-nano fiber membrane

    CN105133183A